Awareness of eating among college students for the health of future generations: University Students’ Awareness of Eating - Kasap, Murat; Tutkun, Erkut (Progress in Nutrition, 2023)
Abstract. Background and aim: The purpose of this study is to investigate the eating awareness levels of undergraduate university students. The sample for the study comprised of 400 volunteer students from various faculties at Bursa Uludağ University who were chosen at random. Methods: The Eating Awareness Scale-30 (EAS-30), which was adapted to Turkish by Köse et al. (2016) and analyzed for reliability-validity, was used as a data collection tool in the study. The study group’s data; normality distribution, T-Test in pairwise comparisons, Anova analysis in three or more comparisons, and Pearson correlation comparison in cause-effect comparisons were all examined at the p<.05 and p<.01 significant level. Results: According to the study’s findings, male students exhibit higher Eating Control (p=.030), Awareness (p=.001), Conscious Eating (=.001), and lower Emotional Eating (p=.001). Female students’ mean BMI values were found to be lower than male students’ (p=.001). It was found that male students of the Faculty of Education had the highest Eating Control (p=.047) and the lowest mean BMI (p=.022) (r= -0.149; p<.016) were very strongly negatively related. Conclusions: All of the students in the research are neither overweight or obese and have a normal BMI. It is advised that kids in late adolescence receive eating awareness instruction, since awareness should be raised for a healthy generation.